Safety and quality of perioperative anesthesia care–Ensuring safe care for older people living with frailty. Issue 1 (May 2021) - Derwall, Matthias; Coburn, Mark
Abstract : The clinical concept of frailty as a detectable and improvable clinical condition has emerged in the field of geriatric medicine over the past two decades. Albeit frailty can be described as the rapid deterioration of organ function during the physiological aging process, this syndrome is not exclusively limited to the elderly. Recently, this concept has been introduced in the field of anesthesia and critical care as a means to better appraise perioperative risks and offer patient-centered individual treatment pathways. Extensive efforts have been invested into the research on tools for the detection and quantification of frailty. However, while multiple tools have been validated for the detection of frailty in different populations, no universal score or test has been validated to be universally applicable. Furthermore, it is unclear whether interventions capable of improving the detected degree of frailty may result in better outcomes. Ongoing and future research is aimed at developing automated systems that help in harnessing standard medical records for reliable frailty screening without additional user input. Further efforts are pointed at understanding the potential reversibility of frailty through interventions such as exercise or nutritional supplements. While the role of frailty detection, quantification, and treatment in anesthesia and critical care is limited today, it is likely that it may become a key element of perioperative care of older patients in the near future.